Detection of IMP-4 and SFO-1 co-producing ST51 Enterobacter hormaechei clinical isolates - Qiao, Jie; Ge, Haoyu; Xu, Hao; Guo, Xiaobing; Liu, Ruishan; Li, Chenyu; Chen, Ruyan; Zheng, Beiwen; Gou, Jianjun (Frontiers in Cellular and Infection Microbiology, 2022)
Purpose: To explore the genetic characteristics of the IMP-4 and SFO-1 co-producing multidrug-resistant (MDR) clinical isolates, Enterobacter hormaechei YQ13422hy and YQ13530hy. Methods: MALDI-TOF MS was used for species identification. Antibiotic resistance genes (ARGs) were tested by PCR and Sanger sequencing analysis. In addition to agar dilution, broth microdilution was used for antimicrobial susceptibility testing (AST). Whole-genome sequencing (WGS) analysis was conducted using the Illumina NovaSeq 6000 and Oxford Nanopore platforms. Annotation was performed by RAST on the genome. The phylogenetic tree was achieved using kSNP3.0. Plasmid characterization was conducted using S1-pulsed-field gel electrophoresis (S1-PFGE), Southern blotting, conjugation experiments, and whole genome sequencing (WGS). An in-depth study of the conjugation module was conducted using the OriTFinder website. The genetic context of blaIMP-4 and blaSFO-1 was analyzed using BLAST Ring Image Generator (BRIG) and Easyfig 2.3. Results: YQ13422hy and YQ13530hy, two MDR strains of rare clone ST51 E. hormaechei harboring blaIMP-4 and blaSFO-1, were identified. They were only sensitive to meropenem, amikacin and polymyxin B, and were resistant to cephalosporins, aztreonam, piperacillin/tazobactam and aminoglycosides, intermediate to imipenem. The genetic context which surrounding the blaIMP-4 was 5ʹCS-hin-1-IS26-IntI1-blaIMP-4-IS6100-ecoRII-3ʹCS. The integron of blaIMP-4 is In823, which the array of gene cassettes of 5ʹCS-blaIMP-4Δ-attC Δ::Kl.pn.I3-3ʹCS. Phylogenetic analysis demonstrated that E. hormaechei YQ13422 and YQ13530 belonged to the same subspecies clusters with a high degree of relatedness. Conclusion: This observation firstly revealed the dissemination of the blaIMP-4 gene in E. hormaechei worldwide. We found that blaIMP-4 and blaSFO-1 co-exist in MDR clinical E. hormaechei isolates. This work showed a transferable IncN-type plasmid carrying the blaIMP-4 resistance gene in E. hormaechei, which has not been reported previously. We examined the potential mechanisms of resistance of pYQ13422-IMP-4 and pYQ13422-SFO-1, along with their detailed genetic contexts.